Lithofacies description and genetic interpretation of San Luis Formation Metaconglomerates (Upper Proterozoic - Cambrian) in Sierra de San Luis, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Sierra de San Luis is part of the southern region of Sierras Pampeanas and it is composed of an igneous-metamorphic basement, mostly generated during the Pampean and Famatinian orogenies. The low-grade metamorphic rocks belong to the San Luis Formation (Prozzi & Ramos, 1988), and they include phyllites, slates, metapsammites, metaconglomerates and acid metavolcanic rocks. This unit is exposed in the south-central sector of the Sierra de San Luis, across two NNE – SSW elongated outcrops called Eastern and Western Belts, which are 50 and 40 km long, respectively (Fig. 1) (Ortiz Suárez et al., 1992). The complex deformational structure of the San Luis Formation hinders its original thickness, estimated at a minimum of 3500 m without decompaction (von Gosen and Prozzi, 1996). According to different dating techniques, the age of the San Luis Formation would span between the Late Neoproterozoic to the Cambrian (Söllner et al., 2000; Drobe et al., 2009, 2011; Casquet et al., 2014). The aim of this paper is to describe and interpret the preserved sedi- mentological features of coarse-grained units within the San Luis Formation (metaconglomerates), in order to shed light into depositional processes and systems. This research is particularly important due to the little knowledge available about the protolite sedimentologic and stratigraphic characteristics of the unit. Additionally, metaconglomerates might constitute a relevant element of stratigraphic corre- lation between different exposures of the San Luis Formation, thus providing time lines that are not possible to obtain by other means. Three main metaconglomerates are reported in this study, one for the Eastern Belt, and two for the Western Belt (Fig. 2). Conventional sedimentological information was collected in the field while logging stratigraphic section. The mineralogy and petrology of the coarse clastic fraction were studied in the field and samples of mudstones and sandstones were collected for microscopic analysis (Table 1). Cañada Honda Metaconglomerate (Prozzi, 1990). This unit is exposed in the Eastern Belt, at Tres Pasos locality(Figs.1,3).This metasedimentite is 270m thick and 10 km along strike. Here, this metaconglomerate has been divided into three sections. The lower section is 60 m thick and consists of disorganized, matrix-supported paraconglomerates (Cfm) (Fig. 4), with up to 30% of framework of pebbles to boulders, and over 70% of muddy matrix with low proportion of sand. Beds commonly have irregular geometries, probably due to the metamorphic deformation, and are thick to very thick bedded. They are interbedded with massive mudstones (Fm), which are up to 0.5 m thick. The second section is 40 m thick and is composed of lenses of normal-graded sabulites (Sg) with erosive bases and scarce lateral development, interbedded with massive mudstones (Fm) (Fig. 5). The upper section is 170 m thick and comprises two paraconglomerates. One of them (Caa) has a 40% of disorganized framework of pebbles and a mud–rich sandy matrix dominated by fine to coarse sand. The other one (Cac) has up to 70% of framework and a mud–rich sandy matrix dominated by fine to coarse sand, with disorganized fabric and uncommon inverse gradation in the first 10 cm of some thick beds. Moreover, coarse pebbles and cobbles (5 to 20 cm long) are commonly observed protruding from the top of the beds (Fig. 7b). Both massive paraconglomerates (Caa and Cac) have tabular geometries with thick to very thick beds. They have flat to slightly erosive bases and transitional tops to fine-grained wackes (Vf) (Fig. 8), which are mostly tabular, thin- to medium-bedded layers. These facies are capped by thin, laminated mudstones (Fl). Four facies associations are recognized in the Cañada Honda Metaconglomerate (Fig. 13a-d). Association Cfm–Fm is interpreted as deposits from cohesive debris flows (Lowe, 1982; Mulder and Alexander, 2001), ending with settling processes associated with residuary particles suspended above those flows (Fig. 13a). Association Sg-Fm is interpreted to reflect deposition from waning turbidity currents with decreasing density (Lowe, 1982) (Fig. 13b). Associations Cac-Vf-Fl and Caa-Vf-Fl are interpreted as deposits of hyperconcentrated cohesionless flows (Mulder and Alexander, 2001), ending with settling processes associated to residuary particles suspended above those flows (Fig. 13c, d). All together, the four facies associations of this metaconglomerate would have deposited in the canyon area of a slope depositional system. Arroyo Curtiembre Metaconglomerate (Ramos et al., 1996). This unit is exposed in the headwaters of the homonymous creek in the northern sector of the Western Belt, where it attains 115 m in thickness and it extends over 2 km along strike (Fig. 9). It is composed of laminated pebbly mudstones (FGl), with 15% of framework of coarse pebbles and 85% of muddy matrix (Fig. 10). The clasts disturb the lamination at their bases and are interpreted as dropstones (Fig. 11a). Beds have tabular geometry and are medium- to thick-bedded. They are typically interbedded with laminated mudstones (Fl) in strata of similar thickness, with transitional contacts (Fig. 11b). Systematic vertical relationship between facies Fl and FGl (Fig. 13e) is inferred to reflect deposition from rain-out of debris, from icebergs and seasonal sea-ice, associated with continuous settling of suspended sediment in low-density plumes, in the maximum proglacial zone. Cerro Blanco Metaconglomerate (new name). This coarse-grained unit is exposed in the eastern side of the homonymous hill in the Western Belt, where it is 35 m thick and no more than 300 m wide. It is composed of laminated pebbly mudstones (FSl) with up to 15% of framework of granules to coarse pebbles (0.2 - 3 cm) and over 85% of muddy matrix (Fig. 12). As in the previous case, the clasts slightly disturb the lamination at their bases, and are, thus, interpreted as dropstones (Fig. 12). Beds are tabular, less than to 2 m thick, and they vertically grade into laminated mudstones (Fl). The close relationship between facies FSl and Fl (Fig. 13f) suggests that this association was formed by the same processes that accumulated the sediments of the Arroyo Curtiembre metasedimentite; that is to say rain-out of debris from icebergs with season fluctuations. In this location, however, there are a lower proportion of pebbles versus matrix and, in average, a smaller grain size (granules vs. pebbles). Considering the marked similarity in facies between Cerro Blanco Metaconglomerate and Arroyo Cur- tiembre Metaconglomerate, we conclude they would represent the same stratigraphic interval.
Keywords: Metaconglomerate, Debrite, Ice-rafted diamictite, San Luis Formation, Sierras Pampeanas.